Efektifitas Terapi Hypno EFT Untuk Menurunkan Dampak Emosi Destruktif Pada Mahasiswa PTKIN Di Kota Salatiga - Qurrotu Ayun (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas AKI Semarang, 2021)
This study aims to test empirically the influence of hypno EFT therapy to reduce the impact of destructive emotion on the students. Participants in this study were students of Islamic Religious Higher Education in Salatiga City. Determination of participants based on pre test scores ranging from 51 to 100 with novaco anger inventory scale and SUD scale from 0 to 10. Subjects in this study amounted is four students who scored high on both scales. The type of research used is experimental research that belongs to the pretest postest one group design. Analysis of data using Wilcoxon Sign Rank Test. Intervention techniques in this study using hypno EFT therapy, which is a therapeutic technique that combines hypnotic conditions in the subject of research with EFT therapy. The results showed that hypno EFT therapy is effective to reduce the impact of destructive emotion on the students.